Aktivasi Media Sosial PT Tourezia Cakra Inspira untuk Meningkatkan Keterlibatan Pengguna - Guantantya, Aurell Salsa; Muslichah, Istyakara (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
This community service activity was carried out by students and lecturers from the Management Study Program at the Islamic University of Indonesia in collaboration with PT Tourezia Cakra Inspira. The background to this activity is the importance of utilizing social media in supporting a company's digital marketing strategy, particularly in the travel and event organizer business sector, which relies on visual content and interaction with audiences. The objective of the activity was to assist PT Tourezia Cakra Inspira in optimizing its digital marketing strategy through the use of social media, specifically Instagram and LinkedIn, as a means to enhance user engagement. The implementation methods included participatory observation during the internship period in the digital marketing division, in-depth interviews with Instagram and LinkedIn followers of PT Tourezia Cakra Inspira, and documentation of the company's social media performance reports. The results of the community service activity indicate that the audience is interested in visual content such as documentation of tours and events, as well as information about tourist destinations. Additionally, user engagement can be enhanced through interactive, educational, consistent content that includes detailed information about services or promotions. The impact of this activity is an increased understanding of the company's audience content preferences, the development of a more relevant digital marketing strategy, and increased user engagement potential on Instagram and LinkedIn for PT Tourezia Cakra Inspira.